2019
DOI: 10.3390/s19051207
|View full text |Cite
|
Sign up to set email alerts
|

Estimating PM2.5 Concentrations Based on MODIS AOD and NAQPMS Data over Beijing–Tianjin–Hebei

Abstract: Accurately estimating fine ambient particulate matter (PM2.5) is important to assess air quality and to support epidemiological studies. To analyze the spatiotemporal variation of PM2.5 concentrations, previous studies used different methodologies, such as statistical models or neural networks, to estimate PM2.5. However, there is little research on full-coverage PM2.5 estimation using a combination of ground-measured, satellite-estimated, and atmospheric chemical model data. In this study, the linear mixed ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“… 97 There are several factors needed to be considered in developing and calibrating the PM levels, including geographical location, meteorological/climate conditions and aerosol optical depth. 97 , 98 Most studies employed a spatiotemporal prediction model by adjusting the subjects’ geographical or residential location. However, some studies did not describe how individual PM exposure estimation was performed or PM modelling was developed.…”
Section: Discussionmentioning
confidence: 99%
“… 97 There are several factors needed to be considered in developing and calibrating the PM levels, including geographical location, meteorological/climate conditions and aerosol optical depth. 97 , 98 Most studies employed a spatiotemporal prediction model by adjusting the subjects’ geographical or residential location. However, some studies did not describe how individual PM exposure estimation was performed or PM modelling was developed.…”
Section: Discussionmentioning
confidence: 99%
“…In total, the correlation between estimated and measured PM 2.5 concentration is more higher in spring and autumn. The In our study, even though the complicated PM 2.5 concentration distribution in Beijing, the modified corrected AOD-PM 2.5 models achieved higher model fitting R 2 values than those in previous studies, e.g., an observation-based algorithm that considers the effect of the main aerosol characteristics applied to the Beijing-Tianjin-Hebei region with R 2 of 0.70 [3], the GWR model applied to the whole China mainland with an overall R 2 of 0.64 [5], an improved model applied to the Beijing-Tianjin-Hebei region with an R 2 of 0.77 [15], satellite-driven PM 2.5 models with VIIRS nighttime data applied to the Beijing-Tianjin-Hebei region with R 2 of 0.75 [19], and NAQPMS data incorporated to MODIS data applied to the Beijing-Tianjin-Hebei region from January to December 2017 with seasonal R 2 values of 0.75, 0.62, 0.80, and 0.78 in the spring, summer, autumn, and winter, respectively [22]. Table 3 is comparison between estimated and measured seasonal average PM 2.5 concentration of 15 monitoring stations from 2014 to 2016.…”
Section: Resultsmentioning
confidence: 99%
“…However, it performs unsatisfactorily in urban regions. The DB algorithm performs better than the DT algorithm over urban areas, and it can provide better land coverage over both dark and bright surfaces, which is more reasonable for PM 2.5 concentration distribution research in Beijing [ 20 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…In other words, AOD gives information about how much direct sunlight is prevented from reaching the ground by aerosols. Furthermore, it gives an estimation of PM2.5 surface concentration [56]. Measurements using satelliteborne observation and aerosol reanalysis products revealed that during lockdown (24th Mar -22nd Apr 2020) maximum decrement in AOD value is observed in eastern IGP ($40% of pre-lockdown; 20th Feb-20th Mar 2020) followed by northwest (27%) and south-India (13%) [4].…”
Section: Aerosol Optical Depth (Aod)mentioning
confidence: 99%